Do student internships build capability? – What OHS graduates really think. (January 2019) - Madigan, Cassandra; Johnstone, Kelly; Cook, Margaret; Brandon, Jason
Highlights: Internships foster development of OHS capabilities. Exposure to OHS professionals and authentic work cultivates professional identity. Development of OHS professional practice skills builds employability. Factors that mediate outcomes are supervision, learning opportunities, and payment. Abstract: Work experience and internships provide students with a vehicle for transferring the advanced knowledge and skills acquired through their academic education into a work setting. At the University of Queensland, Bachelor of Occupational Health and Safety Science (Honours) students undertake compulsory internships (known as student placements) in their final year. The overall aim of this study was to explore the role of the placements in developing Occupational Health and Safety (OHS) professional capability, OHS professional identity, and employability; from the perspective of the OHS graduates. A further aim was to identify factors that mediate student placement experiences. Data was gathered from graduates (n = 27) relating to key OHS knowledge and skills areas, OHS employability, and relationship with host supervisors. The new Global OHS Professional Capability Framework developed by the International Network of Safety and Health Practitioner Organisations (INSHPO), was found to be a useful tool for this evaluation. The majority of the graduates reported that the placement provided an opportunity to apply their OHS knowledge and to further develop their practical OHS skills. Similar to research from other disciplines, the learning outcomes were higher when graduates reported a good relationship with their workplace supervisor, carried out meaningful and relevant work, and received payment from the host organisation. The placements played a greater role than anticipated in the fostering of OHS professional identity, with graduates reporting a greater understanding of the OHS role and professional practice skill development.